Malawi [In Agricultural Extension] - Ragasa, Catherine; Mthinda, Catherine (International Food Policy Research Institute, 2020)
A number of initiatives are being implemented in response to this identified need. Among them, the United States Agency for International Development (USAID) implemented a five-year project (Strengthening Agricultural and Nutrition Extension [SANE]), and the European Union currently funds a five-year project (KULIMA), both of which primarily focus on extension services and their links to agricultural research. Malawi’s Ministry of Agriculture, Irrigation and Water Development (MoAIWD) has also requested a study to look closely at the state of extension services provision, with the intent to further strengthen it to contribute to food security, economic growth, and other development goals. This has led to the three-year project (Assessing and Enhancing the Capacity, Performance, and Impact of the Pluralistic Agricultural Extension System in Malawi), funded by the government of Flanders and the German Agency for International Development, led by the International Food Policy Research Institute (IFPRI). This chapter summarizes the assessment data collected from this IFPRI project, synthesizes its research papers, and extensively reviews relevant literature on the evaluation of extension services approaches in Malawi. The chapter is structured following the best-fit framework discussed in Birner et al. (2009) and presented in Chapter 2.